The Bosnian church and stećci medieval tombstones - Dautović, Dženan (Historical Thought, 2025)
This paper is dedicated to the relations between two phenomena so characteristic for the medieval Bosnian history: one being the monastic order krstjani from Bosnia, ie. the Bosnian Church and the other are medieval tombstones - stećci. During the development of the historiography, attitudes of medievalists regarding these phenomena went through different phases, from almost unconditional connections between them, to the modern stance when it was determined that they were linked, but not exclusively. The sources for the analysis are the epitaphs written on the tombstones, which were confirmed to have belonged to members of the Bosnian church, as well as those tombstones which contain the symbols of a cane and a book which historiography recognizes as signs of spiritual status of the deceased.